2004
DOI: 10.1097/01.ju.0000135303.96496.ee
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Clinical Relevance of Partial Androgen Deficiency of the Aging Male?

Abstract: T values in our study sample did not correlate with clinical signs and symptoms of hypogonadism. Thus, according to our data, symptoms of the aging male could be rather multifactorial and should not be indiscriminately assigned to the age associated decrease in T levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 21 publications
2
25
2
Order By: Relevance
“…Although Chinese cohort studies have tried to establish androgen defi ciency risks by using the IIEF-5 (28), in the majority of studies (29)(30)(31) including the Massachusetts Male Aging Study (MMAS), this correlation was not demonstrated (32). A possible explanation for the differences in these results was suggested in Mikhail's review (33).…”
Section: Discussionmentioning
confidence: 82%
“…Although Chinese cohort studies have tried to establish androgen defi ciency risks by using the IIEF-5 (28), in the majority of studies (29)(30)(31) including the Massachusetts Male Aging Study (MMAS), this correlation was not demonstrated (32). A possible explanation for the differences in these results was suggested in Mikhail's review (33).…”
Section: Discussionmentioning
confidence: 82%
“…Other screening questionnaires have similar constraints. 12,13 In the elderly, the diagnosis of hypogonadism is more problematic because of the difficulty in determining the extent of symptoms caused by aging, hypogonadism or both. 10 Symptomatology provides only 48% sensitivity and 66% specificity for diagnosing hypogonadism.…”
mentioning
confidence: 99%
“…Clinical features suggestive of hypogonadism in the aging male Table 1 footnote. 18 There is sparse evidence concerning ethnic variation in male sex hormones. In a recent study, TT, cFT, and SHBG were lower in Pakistani men than in Afro-Caribbean and Caucasian men living in England.…”
Section: Discussionmentioning
confidence: 99%